Barriers and Determinants of Antenatal Care Utilization among Marginalized Kumal Women in Rainas Municipality, Lamjung, Nepal (The Journal of DMC, 2026)
This study investigates the utilisation of antenatal care (ANC) services among women in Kumal, Rainas Municipality, Lamjung, Nepal, focusing on the frequency of ANC visits and associated socio-demographic factors. A cross-sectional quantitative survey was carried out in 2024 among 322 married Kumal women aged 15–49 years who had experienced a live birth or stillbirth within the past year. Despite national guidelines recommending at least four ANC visits, findings show that most (67%) of respondents reported attending only three visits, with only 29% meeting or exceeding th e recommended number. Chi-square analysis indicated that maternal age (p = 0.032), number of children (p = 0.032), husband’s education (p = 0.000), food sufficiency (p = 0.028), and husband’s foreign employment status (p = 0.034) were significantly associated with ANC visit frequency. In contrast, the mother’s education, sex of the last child, and household headship did not have statistically significant associations. Women aged 34–49 years and those from food-secure households or with migrant husbands were more likely to complete four or more visits. These findings highlight ongoing disparities in ANC utilisation among marginalised groups, influenced by economic, educational, and structural barriers. The study recommends targeted community-based interventions, increased male engagement in maternal health education, and enhanced outreach by health institutions to improve ANC uptake and reduce maternal and neonatal health risks in the Kumal community.